Dendrimers, dendrons, and dendritic polymers : discovery, applications, and the future - Tomalia, Donald A., 1938-; Christensen, Jørn Bolstad; Boas, Ulrik (Cambridge University Press, 2012)
"Dendrimer science has exploded onto the polymer science scene as the fourth major class of polymer architecture. Capturing the history of dendrimer discovery to the present day, this book addresses all the essential information for newcomers and those experienced in the field, including: Fundamental theory, chemistry and physics of the 'dendritic state'; Synthetic strategies (click chemistry, self-assembly, and so on); Dendron/dendrimer characterization techniques; Architecturally driven 'dendritic effects'; Developments in scientific and commercial applications; Convergence with nanotechnology, including dendrimer-based nanodevices, nanomaterials, nanotoxicology and nanomedicine; Dendrimers as a window to a new nano-periodic system. Including first-hand accounts from pre-1995 pioneers, progress in the dendrimer field is brought to life with anticipated developments for the future. This is the ideal book for researchers in both academia and industry who need a complete introduction to the 'dendritic state' with a special focus on dendrimer and dendron polymer science"--Vydavatelská anotace
Keywords: dendrimery; makromolekuly; polymery; supramolekulární chemie; chemická struktura; dendrimers; macromolecules; polymers; supramolecular chemistry; chemical structure; monografie; monographs